COMMUNITY CUSTOM AND FORM OF CHARACTER RESISTANCE IN MEMANG JODOH BY MARAH RUSLI (A STUDY OF IAN WATT'S LITERATURE SOCIOLOGY) - Rahmania Kuku (Universitas Negeri Gorontalo, 2022)
This qualitative descriptive research aimed describe community customs and form of character resistance in